Granulomatosis With Polyangiitis Mimicking Temporal Arteritis - Ali Dehghan; Mahya Sadat Emami Meybodi; Shokoofeh Fooladmotlagh; Mohsen Zaremehrjardi; Hamidreza Soltani (Case Reports in Rheumatology)
This case represents the first diagnosis of pachymeningitis due to granulomatosis with polyangiitis (GPA) in an elderly Iranian man who initially presented with persistent daily headaches. PCR tests of cerebrospinal fluid for tuberculosis, brucellosis, and fungal infections all yielded negative results. Given the pachymeningitis pattern observed on brain MRI and the absence of infectious and lymphoma diseases, along with positive anti-PR3 and proteinuria (793 mg in a 24-h urine sample), a diagnosis of GPA was established. The patient was treated with five doses of pulse methylprednisolone and one dose of pulse cyclophosphamide (1 g). Additionally, prednisolone 60 mg daily, monthly pulse cyclophosphamide, a daily calcium-D tablet, and alendronate 70 mg weekly were prescribed. Subsequently, the patient’s headaches, hearing loss, and vision loss were completely resolved. GPA should be considered in older individuals with persistent daily headaches, especially when pachymeningitis is evident. The use of contrast-enhanced brain MRI is an essential diagnostic tool in such cases.